Hypoxia-Induced Mesenchymal Stem Cell Exosomes Modulate Protein Kinase A and VEGFR Expression in Ultraviolet B-Induced Hyperpigmentation in Mice - Andavania, Sheila Jessica; Syamsunarno, Mas Rizky; Putra, Agung; Setiawan, Eko (Molecular and Cellular Biomedical Sciences, 2025)
Background: Hyperpigmentation is often exacerbated by ultraviolet-B (UVB) exposure through oxidative stress and activation of pathways like mitogen-activated protein kinase (MAPK) and vascular endothelial growth factor receptor (VEGFR). Current treatments carry risks and necessitate safer alternatives. This study investigated the therapeutic potential of hypoxia-induced mesenchymal stem cell (MSC) exosomes in reducing protein kinase-A (PKA) and VEGFR expression in UVB-induced hyperpigmentation.Materials and methods: A post-test-only control group design was used with 30 male C57BL/6 mice divided into five groups: Healthy group, 0,9% NaCl-treated group, retinol-treated group, and two treatment groups (200 µL Exosomes-treated group and 300 µL Exosomes-treated group. UVB-induced hyperpigmentation was established with 180 mJ/cm² exposures over two weeks. Treatment was administered via subcutaneous injections for seven days. PKA and VEGFR mRNA levels were analyzed using qRT-PCR.Results: PKA expression was significantly lower in the 200 µL Exosomes-treated group (0.34±0.05) and 300 µL Exosomes-treated group (0.21±0.04) groups compared with the 0,9% NaCl-treated group (1.12±0.08) (p<0.001). VEGFR expression similarly decreased in 200 µL Exosomes-treated group (0.32±0.05) and 300 µL Exosomes-treated group (0.18±0.04) versus the 0,9% NaCl-treated group (1.48±0.09) (p<0.001). Both exosome doses achieved reductions comparable to baseline levels observed in the Healthy group.Conclusion: Hypoxia-induced MSC exosomes reduced PKA and VEGFR expression in UVB-induced hyperpigmentation, with the 300 µL dose showing greater efficacy. These findings suggested exosome therapy as a promising alternative for hyperpigmentation treatment. Keywords: hyperpigmentation, MSC, PKA, VEGFR, melanin